(untitled) (Acta Scientiarum. Biological Sciences, 2024)
The study aimed to assess species richness and diversity in Aquidauana, State of Mato Grosso do Sul, using six observation points over 12 months. A total of 2,591 individuals among reptiles, birds, and mammals, covering 29 orders and 43 families, were recorded. Columbidae, Furnariidae, and Tyrannidae were prominent families, and Passeriformes was the most representative order. The point with the highest number of observations was near Lagoa Comprida, probably due to minimal human disturbance. The most observed species included Rufous hornero, Wattled jacana, Black-bellied duck, and Whistling-duck. December was the month with the highest number of sightings. Nine feeding guilds were identified, and three species were classified as vulnerable or near threatened. The bootstrap estimator suggested the potential for finding more species with increased sampling. The Shannon index revealed no significant difference between observation points. Aquidauana presents notable urban biodiversity, emphasizing the importance of conserving wetlands and forest areas to preserve diversity.